PENGARUH PENCUCIAN DAN PENAMBAHAN CRYOPROTECTAN PADA KARAKTERISTIK SURIMI IKAN PATIN (Pangasius sp.) - Hafiluddin, Hafiluddin (Rekayasa, 2012)
Catfish are traded in the form of whole fish and fillet products. Catfish are still not widely used or processed into value added products. The purpose of this study was to determined the effect of frequency of washing and frozen storage of catfish surimi characteristics. The research was conducted with several stages, they were to determined the characteristics of raw materials and to made within difference of washing frequencies to determined the best surimi; second, this study also to determined the effect of storage duration on physical and chemical characteristics of catfish surimi. The best of catfish surimi production due with once washing. It was based on test of fold, teeth cutting and water content. Storage treatments and cryoprotectan additional give different results on the value of TVB, pH and water content catfish surimi. The value of TVB, pH dan water content also increased. Hidonik test (folding and teeth cutting test) also shows the different results between the different treatment of both storage and cryoprotectan addition. During storage, the folding and teeth cutting test remains in good value which indicates deterioration in the quality of catfish surimi occurred slowly.